Effect of Exercise on Fatigue in Multiple Sclerosis Patients: A Network Meta-analysis - Chen, Yuting; Xu, Shanshan; Shen, Jiran; Yang, Hui; Xu, Wei; Shao, Ming; Pan, Faming (International Journal of Sports Medicine, 2021)
Few studies have directly compared the effects of different exercise therapies on reducing fatigue in patients with multiple sclerosis. Thus, we conducted a Frequentist network meta-analysis to analyze and compare the effectiveness of different types of exercise on reducing multiple sclerosis-related fatigue. Relevant randomized controlled trials were searched in PubMed, Web of Science and Cochrane Library databases from the date of their inception up to April 1, 2021. In total, 27 articles involving 1470 participants and 10 types of interventions met the inclusion criteria. The results indicated that aquatic exercise ranked as the most effective among these interventions, and aerobic exercise had small-to-moderate effect sizes. Most of the interventions were shown to be better than the control group, except for climbing. Climbing was the only intervention that ranked worse than the controls. All of these findings merit further investigation in future clinical trials.
Keywords: multiple sclerosis; fatigue; exercise; training; ranking